2001
DOI: 10.1152/ajpheart.2001.281.3.h1137
|View full text |Cite
|
Sign up to set email alerts
|

Altered SR protein expression associated with contractile dysfunction in diabetic rat hearts

Abstract: The goal of this study was to examine whether alteration of sarcoplasmic reticulum (SR) protein levels is associated with early-onset diastolic and late-onset systolic dysfunction in streptozotocin (STZ)-induced diabetic rat hearts. Four-week diabetic rat hearts exhibited slow relaxation, whereas 6-wk diabetic rat hearts exhibited slow and depressed contraction. Total phospholamban level was increased, and phosphorylated level was decreased in 4- and 6-wk diabetic rat hearts. Sarco(endo)plasmic reticulum Ca(2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
94
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 33 publications
10
94
1
1
Order By: Relevance
“…Interestingly, it has been reported that hyperglycemia-induced cardiomyocyte apoptosis is due in part to impaired SERCA function (11), the same mechanism of action of thapsigargin. Rodent models of both type 1 and type 2 diabetes display reduced SERCA2a function, lengthened relaxation times, and impaired contractility (2,3,5,22,53,62). In cardiomyocytes, SERCA2a controls the removal of cytosolic Ca 2ϩ and the storage of Ca 2ϩ in the sarco/endoplasmic reticulum (24).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been reported that hyperglycemia-induced cardiomyocyte apoptosis is due in part to impaired SERCA function (11), the same mechanism of action of thapsigargin. Rodent models of both type 1 and type 2 diabetes display reduced SERCA2a function, lengthened relaxation times, and impaired contractility (2,3,5,22,53,62). In cardiomyocytes, SERCA2a controls the removal of cytosolic Ca 2ϩ and the storage of Ca 2ϩ in the sarco/endoplasmic reticulum (24).…”
Section: Discussionmentioning
confidence: 99%
“…The formation of collagen advanced glycation endproducts (AGE) due to hyperglycaemia is associated with LV chamber stiffness [23], and exposure to AGE or overexpression of the AGE receptor is associated with abnormal intracellular calcium handling [24] and thus abnormal myocardial relaxation. Insulin therapy has been shown to reverse passive-elastic changes in diabetic rats [18] and to normalise sarcoplasmic reticulum protein expression and function [25]. Furthermore, progressive structural changes in the myocardium caused by diabetes might be prevented by early insulin treatment and selectively reversed by delayed insulin treatment [26].…”
Section: Discussionmentioning
confidence: 99%
“…The density of proteins from the hypoxic rat and its corresponding age-matched normoxic control rat run in the same gel were compared, and the level of each protein sample in the hypoxic rat heart was expressed as a percentage of that in its age-matched control sample in the same gel. This analysis procedure can effectively eliminate not only the possible false results due to errors during protein loading, separation, and transfer but also the variations among experiments in protein density determinations of the bands (8, 25,41).…”
Section: Methodsmentioning
confidence: 99%